2008
DOI: 10.1016/j.etap.2007.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of PCBs induces proinflammatory and prometastatic responses

Abstract: Exposure to specific congeners of polychlorinated biphenyls (PCBs) can induce proinflammatory alterations, which may contribute to the formation of blood-borne tumor metastasis. The main aim of the present study was to establish an experimental model of PCB exposure in which PCBs are administered by oral gavage, which resembles the human exposure through the food chain. To determine structure-function relationship, we studied induction of inflammatory responses in the livers, lungs and brains of mice treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Among ortho-substituted PCBs, 2,2',4,5,6'-pentachlorobiphenyl (PCB104) also affects tight junction proteins expression in brain endothelial cells, stimulates inflammatory mediators in vascular endothelial cells and induces prometastatic responses (Choi et al 2003, Sipka et al 2008. It has been demonstrated that vascular endothelial growth factor (VEGF) is involved in PCB104 induced endothelial hyperpermeability (Eum et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among ortho-substituted PCBs, 2,2',4,5,6'-pentachlorobiphenyl (PCB104) also affects tight junction proteins expression in brain endothelial cells, stimulates inflammatory mediators in vascular endothelial cells and induces prometastatic responses (Choi et al 2003, Sipka et al 2008. It has been demonstrated that vascular endothelial growth factor (VEGF) is involved in PCB104 induced endothelial hyperpermeability (Eum et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on PCB toxicity are mainly based on in vitro models or in vitro experiments in which mice or rats are intraperitoneally injected with PCBs (Sipka et al 2008). The in vivo effects of PCB153 and PCB104 on expression of the VEGF system in the CP in domestic animals exposed to PCBs through the food chain, the most common route of PCB exposure, has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCB-77, PCB-104 and PCB-153 induced expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and monocyte chemoattractant protein-1 (MCP-1) in the liver, lung, and brain of male C57Bl/6 mice. PCB-77 and PCB-104 also increased levels of matrix metalloproteinase-7 (MMP-7) mRNA in the liver and brain (Sipka et al, 2008).…”
Section: (C) Other Cellular Mechanisms Relevant To Pcbinduced Carcinomentioning
confidence: 99%
“…In addition to the core groups, inflammation, albeit of low incidence and intensity, was also observed in the control groups in the studies with PCB-118 and PCB-126, and in the uterus of rats in the PCB-153 control group, but not in the ovary of rats in the same group. Sipka et al (2008) investigated the potential for various PCB congeners to induce inflammation in mice. Mice were given a single gavage dose (150 μmol/kg bw) of PCB-77, PCB-104, or PCB-153.…”
Section: (Ii) Pcb Congenersmentioning
confidence: 99%